Novel fan configuration for distributed propulsion systems with boundary layer ingestion on an hybrid wing body airframe - Valencia, Esteban; Alulema, Victor; Rodriguez, Dario; Laskaridis, Panagiotis; Roumeliotis, Ioannis (Elsevier, 2020)
The performance benefits of directly ingesting the boundary layer (BLI) on air vehicles with distributed propulsion (DP) systems has been documented and explored extensively. However, numerous investigations have demonstrated that the increase of the flow distortion in the inlets of conventional propulsors can dramatically reduce the expected benefits. Hence, this work presents an alternative fan configuration to re-energize the boundary layer, and at the same time, to perform properly in a distorted and non-uniform flow-field. This conceptual design utilizes a two-dimension idealized fan and replaces the rotational movement with linear displacement, avoiding the undesired effects of circumferential distortion on the propulsor operation. A quasi two-dimensional model based on the Discretized Miller approach has been used to compare the proposed configuration with a conventional axial fan. From the results obtained, it is observed that the thermal performance of the fan is less affected for the proposed configuration and furthermore, intake pressure losses are ameliorated by the use of a single mailbox shape inlet. The performance assessment of the proposed configuration coupled on the N3-X aircraft shows benefits of 4% in fuel savings compared with current BLI turbo-machinery configurations. The main contribution of this study lies on the definition of a preliminary design for an alternative propulsor configuration able to deal with circumferential distortion.